The effect of shielding, grounding and bonding to the electromagnetic compatibility of high emission printed circuit board - Mohammed Nwehil, Aghssan (2018)
Electromagnetic Compatibility (EMC) is the capability of the device or the system to perform its work correctly within its electromagnetic environment without causing the introduction of electromagnetic damage to that environment. Radiated Emission (RE) is one of the EMC tests that should be conducted to ensure that the product or equipment do not radiate any unwanted Electromagnetic (EM) to its environment. In this work, three different types of Printed Circuit Board (PCB) designs are studied. The PCBs are less costly and can be easily protected from the impact of the electromagnetic environment from the EM radiation. The effect of two high radiation circuits on each other has been studied and found to be the best way to reduce this bad effect using EMC techniques. Shielding is one of the EMC design to reduce the radiation. However, shielding must be accompanied by grounding to ensure unwanted current has been grounded to the shielded enclosure. Therefore the emission can be reduced an average 10.1 dB μV/m after grounding has been applied. The effect of two equipments without bonding can be useless because non-equipotential occurs. Therefore, bonding has been applied between two enclosures (system), which gave a significant reduction by 8.7 dB μV/m. Based on the study, it shows that the best bonding type is a metal plat joint tightly between two enclosures as compared with big tail wire or braided strap.